Harvesting medicinal plants in forest area of Peninsular Malaysia / Mohd Azmi Muhammed Idris and Awang Noor Abd. Ghani - Muhammed Idris, Mohd Azmi; Abd. Ghani, Awang Noor (2002)
The practice of traditional medicine using medicinal plants from tropical rain forests are still persists despite an advancement of modern medicine. Most of the medicinal plants used by the users, particularly the Malay practitioners, are gathered from the forest. Without proper regulations on management and conservation of medicinal plants, the sustainable harvest of the resources from the forest would be reduced in the future. This may lead to resource depletion and may impose high social cost for the future generation. Increasing demand for medicinal plants in the future will reduce apparent viability of the industry due to high investment cost in management and conservation. Therefore, the government should consider long-term measures to conserve this valuable non-timber forest product. The use of regulations and other measures are vital towards achieving sustainable management of medicinal plants practices. This paper highlights the utilization and harvesting of medicinal plants from the forest, legislation and management aspects related to the resources and also the problem of extinction raised from the over collection by practitioners and industries. Some policy recommendations on medicinal plants resources have also been suggested.